2020
DOI: 10.3390/dj8030096
|View full text |Cite
|
Sign up to set email alerts
|

Mouthwash Effects on LGG-Integrated Experimental Oral Biofilms

Abstract: In order to investigate the effects of mouthwashes on oral biofilms with probiotics, we compared in biofilms the susceptibility to mouthwashes of probiotic Lactobacillus rhamnosus GG (LGG) and oral pathogens Streptococcus mutans, Streptococcus sanguinis, and Candida albicans. We also evaluated these pathogens’ susceptibility to the mouthwashes and their recovery after mouthwash-rinsing in biofilms with/without LGG. First, 1-day-/3-day-old LGG-integrated multi-species biofilms were exposed for 1 min to mouthwas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…For example, Chinnappa et al [24] observed a decrease in S. mutans count after a week-long daily consumption of ice cream and whey containing a probiotic. Similar results were obtained by Caglar et al [6] with Bifidobacterium lactis, Jiang et al [17] with the probiotic L. rhamnosus, Hedayati-Hajikand [11] with ProBiora3® blend of three strains of probiotic bacteria (S. uberis KJ2™, S. oralis KJ3™, S. rattus JH145™), and Burton et al [26] using S. salivarius M18.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, Chinnappa et al [24] observed a decrease in S. mutans count after a week-long daily consumption of ice cream and whey containing a probiotic. Similar results were obtained by Caglar et al [6] with Bifidobacterium lactis, Jiang et al [17] with the probiotic L. rhamnosus, Hedayati-Hajikand [11] with ProBiora3® blend of three strains of probiotic bacteria (S. uberis KJ2™, S. oralis KJ3™, S. rattus JH145™), and Burton et al [26] using S. salivarius M18.…”
Section: Discussionsupporting
confidence: 81%
“…This microorganism is capable of colonizing the oral cavity and thus replacing cariogenic streptococci bound to the tooth surface because the adherent ability of Lactobacillus rhamnosus for oral tissues is greater than the adherent ability of streptococci [15]. Short and long-term intake of probiotics could reduce the caries risk among children, decrease gum bleeding and reduce gingivitis, reduce the pocket depth and positively affect the gain of clinical attachment, as well as reduce the counts of Candida albicans in elderly [17].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the manufacturer's Behsa concentrations in the Kin gingiva mouthwash have not been reported, and studies' attention is not similar (26) . Therefore, Boht may be used every day as the natural component is present in Behsa and the tooth's lack of dental colour potentials (5) .…”
Section: Discussionmentioning
confidence: 99%
“…The primarily mechanical removal of plastic plaque through regular tooth brushing is used to prevent different periodontal diseases' development and progression (4) . The use of mouthwash to control plaque bacteria is about 5000 years long when the Chinese suggested that urine for children be used to prevent gingivitis (5) . Various bacterial and fungal communities integrated into a highly specialised extracellular matrix are present in oral biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Mouthwash helps reduce microbial plaques. 3,4 In some cases, the use of an antiseptic mouthwash for an extended period can cause bacterial resistance. 5 Previous studies reported an increased resistance of Streptococcus mutans to fluoride when used over a long period.…”
Section: Introductionmentioning
confidence: 99%